Five-year Trends in Various Communicable Diseases Reported under the Integrated Disease Surveillance Program during 2014–2019 in Puducherry - K Sivaranjini; Durgesh Roy; Yuvaraj Krishnamoorthy; Ravivarman Lakshmansamy; Srividya Vissvesvaran; G Ragunathan; Mahalakshmy Thulasingam; Sitanshu S. Kar (Indian Journal of Community Medicine)
The current study aimed to determine the trend in the incidence of various communicable diseases reported under the Integrated Disease Surveillance Program (IDSP) in Puducherry. This record-based study obtained disease details in terms of the number of suspected cases reported, tested, and positive for the selected diseases reported under IDSP from 2015 to 2019. Dengue disease has shown a recent declining trend in the number of cases and test positivity (7.2% in 2015 to 5.2% in 2019), and there has been a steady increase in the burden of Chikungunya over the years (4.1% in 2015 to 12.6% in 2019). Malaria has been controlled well in Puducherry, but the testing rate was only 3%–4%, well below the national recommendation of testing 10% of the total population. In 2018, there was a recent increase in influenza cases, with test positivity reaching up to 21%. The study unveils valuable insights into communicable diseases in Puducherry, highlighting the fluctuating burden of vector-borne, water-borne, and influenza infections.